KEANEKARAGAMAN SERANGGA PADA TANAMAN KAKAO (THEOBROMA CACAO L) DI KECAMATAN MARGA KABUPATEN TABANAN - Mahima, N M Anugrah; Martiningsih, Ni Gst. Ag. Gde Eka; Hanum, Farida (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2018)
This study entitled the diversity of insects in cocoa plants (Theobroma cacao L) in Marga District, Tabanan Regency. The implementation began in November 2017. This study aims to determine the types of insects found in cocoa plants. By carrying out observations of land for data collection, starting from taking pictures and counting the number of insects in cocoa plantations. The results show that the one that dominates the type of insect is the small red ant insect Oechophylla smaragdina with 68 tails. Based on the results of the study it can be concluded that the types of insects found in cocoa plantations in the Marga district of Tabanan Regency consist of 8 types of insects namely black ants (Dolichoderus thoracicus smith), large black ants (minimum Monomorium), small red ants (Oechophylla smaragdina), crickets (Gryllidae), Orong-orong (Gryllotalpidae), Beetles (Coleoptera), Spiders (Araneae), Snails (Achatina fulica). It can be suggested that we know the role of each type of insect.